Molecular epidemiology of Campylobacter isolates from broiler slaughterhouses in Tripoli, North of Lebanon. Issue 6 (2nd November 2019) - Rafei, R.; Al Kassaa, I.; Osman, M.; Dabboussi, F.; Hamze, M.
ABSTRACT: 1. The real burden of Campylobacter spp. in Lebanon is still unknown. The aims of this study were to unravel the epidemiology of Campylobacter spp. in broilers at slaughterhouses in Tripoli, North of Lebanon and to characterise their antibiotic resistance profiles. 2. From May to November 2015, sampling was performed through five repeated surveys from 15 slaughterhouses that sold chicken directly to Lebanese customers. Isolates were subjected to pulsed field gel electrophoresis (PFGE) and flaA -restriction fragment length polymorphism ( flaA -RFLP). 3. All investigated slaughterhouses were found to be positive for Campylobacter spp. Campylobacter coli was the predominant species (38 isolates) followed by C. jejuni (eight isolates). A noticeable level of resistance was detected among isolates against ciprofloxacin (97% of C. coli and 87.5% of C. jejuni ), amoxicillin (89% of C. coli and 75% of C. jejuni ), gentamicin (79% of C. coli and 50% of C. jejuni ), and co-amoxiclav (24% of C. coli and 25% of C. jejuni ). Erythromycin and ertapenem resistance were observed only in C. coli with the following percentages 74% and 13% respectively, but not in C. jejuni . PFGE and flaA -RFLP using Dde I as restriction enzyme divided the strains into 27 and 25 types respectively. 4. The high observed genetic diversity of Campylobacter spp. revealed the complexity of the spread of this genus in broilers. This study highlighted the pressing need to monitor antibiotic resistance and to ensure food safety from 'farm to fork' in Lebanon.